His bundle recordings in right bundle-branch block coexisting with iatrogenic right ventricular pre-excitation - Castellanos, Agustin (1972)
Iatrogenic right ventricular pre-excitation failed to abolish right bundle-branch block in two patients. When `exclusive' His bundle pacing was performed, the QRS complexes, St-V, and St-LVE intervals were similar to the ventricular deflections, H-V, and V-LVE (intervals) recorded during sinus rhythm. `Exclusive' pacing of the ordinary muscle at the right ventricular inflow tract produced a complete left bundle-branch block pattern without abnormal left axis deviation. Pacing of both His bundle and ordinary muscle yielded combination complexes in which the right bundle-branch block pattern persisted. The ventricular activation process was studied in these beats, as well as during the right and left bundle-branch block induced by coupled atrial stimulation. It appeared as if certain areas of the right septal surface behaved, electrophysiologically, as if they belonged to the left ventricle. Impulses emerging from these sites were not propagated to the right ventricular free wall. The latter was activated by the excitation front emerging through the left bundle system. During right bundle-branch block the endocardium of the right ventricular inflow was activated before the peak of the R in V(1). Bipolar leads, 1 mm apart (with the possible exception of the ones over the tricuspid valve), were helpful in mapping the spread of activation in the human heart.